1981
DOI: 10.1111/j.1471-4159.1981.tb04669.x
|View full text |Cite
|
Sign up to set email alerts
|

Compartments of Labeled and Endogenous γ‐Aminobutyric Acid Giving Rise to Release Evoked by Potassium or Veratridine in Rat Cortical Slices

Abstract: To establish compartments involved in depolarization-induced release of gamma-aminobutyric acid (GABA) in rat brain slices, the amount of exogenous labeled and endogenous GABA released and retained was followed during 48 min exposure to 50 mM-K+ or to 50 microM-veratridine. Endogenous GABA was measured with high performance liquid chromatography. The presence of 10 microM-aminooxyacetic acid throughout prevented both the metabolism of GABA and the formation of endogenous GABA due to depolarization. During supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…They concluded that newly synthesized GABA is located in a pool different from that of [3H]-GABA taken up into the preparation and is not under the influence of GABA-transaminase. This conclusion is further corroborated by the work of Szerb et al (1981) who demonstrated that inclusion of gabaculline in a superfusion system containing rat cortical slices augmented the depolarization-induced release of [3HJ-GABA but not that of endogenous GABA.…”
Section: Control Ecssupporting
confidence: 64%
See 1 more Smart Citation
“…They concluded that newly synthesized GABA is located in a pool different from that of [3H]-GABA taken up into the preparation and is not under the influence of GABA-transaminase. This conclusion is further corroborated by the work of Szerb et al (1981) who demonstrated that inclusion of gabaculline in a superfusion system containing rat cortical slices augmented the depolarization-induced release of [3HJ-GABA but not that of endogenous GABA.…”
Section: Control Ecssupporting
confidence: 64%
“…endogenous GABA release using tissue slices in a superfusion model (Szerb et al, 1981). Basal tissue levels of GABA measured from the slices after incubation were higher than values obtained from microwave irradiation and the post-mortem rise in GABA levels is the probable explanation for the absence of any difference in basal GABA content between controls and ECS animals.…”
Section: Control Ecsmentioning
confidence: 75%
“…Thus, endogenously and exogenously derived GABA release appear to be differently affected by cocaine sensitization. This is not surprising, however, because of possible differences in endogenous and exogenous GABA incorporation into intraterminal pools and subsequent differences in release in response to various stimuli (Abe and Matsuda, 1983;Lidén et al, 1987;Pin and Bockaert, 1989;Ryan and Toskoski, 1975;Sellström and Hamberger, 1977;Szerb, 1983;Szerb et al, 1981). Neuronal GABA exists in several intraterminal pools (see Fig, 4A): newly synthesized pools (S) and metabolic pools (M) filled via reuptake pumps.…”
Section: Discussionmentioning
confidence: 94%
“…Neuronal GABA exists in several intraterminal pools (see Fig, 4A): newly synthesized pools (S) and metabolic pools (M) filled via reuptake pumps. In these experiments, the released endogenous GABA could originate from both the newly synthesized pools and the metabolic pools (Abe and Matsuda, 1983;Ryan and Toskoski, 1975;Szerb, 1983;Szerb et al, 1981). Depletion of either of these pools could contribute to the decrease in endogenous GABA release seen in cocainesensitized rats (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation